Biomimetic stochastic topography and electric fields synergistically enhance directional migration of corneal epithelial cells in a MMP-3-dependent manner. (15th January 2015) - Gao, Jing; Raghunathan, Vijay Krishna; Reid, Brian; Wei, Dongguang; Diaz, Rodney C.; Russell, Paul; Murphy, Christopher J.; Zhao, Min
Graphical abstract: Abstract: Directed migration of corneal epithelial cells (CECs) is critical for maintenance of corneal homeostasis as well as wound healing. Soluble cytoactive factors and the intrinsic chemical attributes of the underlying extracellular matrix (ECM) participate in stimulating and directing migration. The central importance of the intrinsic biophysical attributes of the microenvironment of the cell in modulating an array of fundamental epithelial behaviors including migration has been widely documented. Among the best measures of these attributes are the intrinsic topography and stiffness of the ECM and electric fields (EFs). How cells integrate these multiple simultaneous inputs is not well understood. Here, we present a method that combines the use of (i) topographically patterned substrates (mean pore diameter 800 nm) possessing features that approximate those found in the native corneal basement membrane; and (ii) EFs (0–150 mV mm −1 ) mimicking those at corneal epithelial wounds that the cells experience in vivo. We found that topographic cues and EFs synergistically regulated directional migration of human CECs and that this was associated with upregulation of matrix metalloproteinase-3 (MMP3). MMP3 expression and activity were significantly elevated with 150 mV mm −1 applied-EF while MMP2/9 remained unaltered. MMP3 expression was elevated in cells cultured on patterned surfaces against planar surfaces. The highest single-cell migration rate was observed with 150 mV mm −1 applied EF on patterned and planar surfaces. When cultured as a confluent sheet, EFs induced collective cell migration on stochastically patterned surfaces compared with dissociated single-cell migration on planar surfaces. These results suggest significant interaction of biophysical cues in regulating cell behaviors and will help define design parameters for corneal prosthetics and help to better understand corneal wound healing.